Controlling the Oosterschelde storm-surge barrier. Vol. III, predicting North Sea water levels : a policy analysis of alternative strategies - Catlett, Louis, 1931-; Hall, Gaineford J.; Rand Corporation; Netherlands. Rijkswaterstaat (Santa Monica, CA : RAND, 1979)
The third in a four-volume study to assist the Netherlands government in a policy analysis of alternative control strategies for operating the storm-surge barrier across the Oosterschelde basin. This volume describes and evaluates several models for predicting North Sea water levels outside the barrier. The models include prediction based on observed local water levels (correlation over time); on observed remote water levels (correlation over space); on observed weather conditions, ranging from very short predictions (1 to 2 hours) to longer predictions (6 to 12 hours) for operational control of the barrier with different potential strategies; and on long-term weather forecasts (24 to 48 hours) for conducting maintenance, providing alert, etc. The statistical techniques explored here are intended to provide the Dutch with a basis for further study of hydraulic conditions in the North Sea as relates to the control of the storm-surge barrier. 90 pp. Ref.
"September 1979."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Dikes (Engineering) -- Netherlands -- Oosterschelde -- Design and construction -- Data processing; Dikes (Engineering) -- Netherlands -- Oosterschelde -- Design and construction -- Mathematical models; Estuarine area conservation -- Netherlands -- Oosterschelde; Flood dams and reservoirs -- Netherlands -- Oosterschelde -- Design and construction -- Data processing; Flood dams and reservoirs -- Netherlands -- Oosterschelde -- Design and construction -- Mathematical models; Storm surges -- Netherlands -- Oosterschelde